Effect of Different Egg Yolk Levels in Tris Extender With and Without Aloe Vera and Onion Crude Extracts on Surti Buck Semen at Refrigerated Temperature - Patel, Dignesh K.; Chaudhari, Chandrakant F.; Modi, Lalit C.; Chaudhari, Naresh F.; Chaudhary, Mahesh M.; Tyagi, Kuldeep K.; Kunvar, Sunil V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study aimed to develop a suitable Tris-citrate-fructose-egg yolk (Tris) based extender with Aloe vera or onion extract to preserve Surti buck semen at refrigerated temperature. Semen ejaculates (n=96) collected by artificial vagina from eight bucks were split-diluted in Tris extender with 0, 5, 10, 20% egg yolk concentrations. All these were then fractionated into three aliquiots each, one fracrtion kept without further additives (EY0, EY5, EY10, EY20), while fractions 2 and 3 were an addition with crude filtrates of Aloe vera gel @ 10 µL (EY0+A, EY5+A, EY10+A, EY20+A) or onion extract @ 10 µL (EY0+O, EY5+O, EY10+O, EY20+O) per 0.5 ml of the extended semen. These samples (4x3 = 12 aliquots, each 0.5 ml) were then preserved at refrigerated temperature and evaluated at 12 hourly interval up to 48 h of storage for various sperm quality tests. Sperm motility was significantly lower (p<0.01) in all the subgroups with 0% egg yolk (EY0, EY0+A, EY0+O) compared to 5 to 20% egg yolk at all intervals. The sperm motility at 48 h was significantly (p<0.01) lower in EY0 without and with Aloe vera and onion (11.49 ± 2.54, 10.12 ± 2.45 and 6.58 ± 2.30 %) than EY5 without and with Aloe vera and Onion extract (53.85 ± 1.41, 56.82 ± 1.20, 34.84 ± 2.25%), EY10 without and with Aloe vera and onion (55.83 ± 1.19, 57.76 ± 1.10, 35.37 ± 2.15%), EY20 without and with Aloe vera and onion extract (56.09 ± 1.32, 56.46 ± 1.26 and 41.06 ± 1.92%, respectively). The live sperm count was significantly lower (p<0.01) in semen extended with 0% egg yolk as compared to 5, 10 and 20% egg yolk at 0, 24 and 48 hours. The post-chilled abnormal sperm percentage increased non-significantly at 24 and 48 hours in all extender combinations, although the effect of additives was non significant. It is concluded that adding egg yolk alone 5–20% or with Aloe vera extract @ 10 µL in semen extender had a beneficial role in Surti buck semen preservation at refrigerated temperature.